Factores socioeconómicos que determinan la desnutrición crónica infantil en niños menores de 3 años en la parroquia Chiguaza, cantón Huamboya, provincia de Morona Santiago. - Orellana Brito, Damaris Keily (2024)
ABSTRACT: The main objective of this research study was to identify the socioeconomic determinants of chronic child malnutrition in Chiguaza parish, Huamboya canton, Morona Santiago province. Chronic child malnutrition, a pathological condition resulting from insufficient absorption of essential nutrients, manifests itself in weight loss, growth retardation and deterioration of general health. A survey, logit, and probit models were apply to analyze the socioeconomic conditions of the population. The sample included 225 children under three years of age belonging to the Creciendo con Nuestros Hijos (CNH) program in the community, revealing eight significant variables: mother's level of education, absence of prenatal and postpartum control, birth order, lack of folic acid intake, number of meals during pregnancy, absence of the father in the home, and father's unemployment. It concluded that there are economic constraints and ingrained gender roles that negatively affect the well-being and development of the parish. Child malnutrition generates immediate medical costs and loss of productivity, while, in the long term, it limits educational and employment opportunities, perpetuating a cycle of intergenerational poverty. Keywords: Chronic child malnutrition, socioeconomic factors, poverty, rural area.